2013
DOI: 10.1097/mpg.0b013e31828b1d90
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Retinol and Lung Function in Young Patients With Cystic Fibrosis

Abstract: FEV₁ of young patients with CF correlates positively with SR, regardless of age, pancreatic function, or nutritional condition. Those with a moderately high retinol (up to 110 μg/dL) maintain the best respiratory function (FEV₁ ≥80% in >90% of them) without any signs of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Some data suggested significant positive correlations between vitamin A concentration and FEV1 in children, adolescent and young adults with CF (Aird et al, 2006;Rivas-Crespo et al, 2013). Rivas-Crespo et al established that 90% of CF patients with a serum retinol concentration up to 110 μg/dL had FEV1 ≥ 80% (Rivas-Crespo et al, 2013). However, Woestenenk et al (2015) in their longitudinal study did not find such a relationship in children and adolescents with CF (n = 228).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Some data suggested significant positive correlations between vitamin A concentration and FEV1 in children, adolescent and young adults with CF (Aird et al, 2006;Rivas-Crespo et al, 2013). Rivas-Crespo et al established that 90% of CF patients with a serum retinol concentration up to 110 μg/dL had FEV1 ≥ 80% (Rivas-Crespo et al, 2013). However, Woestenenk et al (2015) in their longitudinal study did not find such a relationship in children and adolescents with CF (n = 228).…”
Section: Discussionmentioning
confidence: 70%
“…However, these results are very often ambiguous. Some data suggested significant positive correlations between vitamin A concentration and FEV1 in children, adolescent and young adults with CF (Aird et al, 2006;Rivas-Crespo et al, 2013). Rivas-Crespo et al established that 90% of CF patients with a serum retinol concentration up to 110 μg/dL had FEV1 ≥ 80% (Rivas-Crespo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship was illustrated in a large US cohort study where airway function was found to be independently and directly related to serum vitamin A level (4). A similar correlation was also established in children with respiratory tract infection-associated wheezing and adult patients with obstructive lung diseases such as asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (5)(6)(7)(8). In addition, a number of genome-wide association studies (GWAS) identified a genomic locus in the RA receptor-β (RARB) gene to be highly associated with airway function in healthy cohorts and patients with asthma or COPD (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 79%
“…An article recently published in this journal by Woestenenk et al [1] cites a study on young people with cystic fibrosis published by our research group [2].…”
mentioning
confidence: 99%